(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2025)
This paper analyses two prosaic texts by Miguel de Unamuno, “Y va de cuento...” and Cómo se hace una novela. As special attention to the formal aspects of the prosaic text first emerged in Russian poetics in the literary theory of the early 20th century, we chose to analyse Unamuno’s two texts with recourse to Boris Eichenbaum’s theory. We take as point of reference of this paper his essay entitled “The Structure of Gogol’s ‘The Overcoat’”, in which he highlights aspects and narrative techniques that can be related to those we can find in “Y va de cuento...” and Cómo se hace una novela. Thus, in this paper we analyse how the author’s ‘personal tone’, the role or lack of plot and the relevance of the ‘acoustic characteristics’ appear in “Y va de cuento...” and Cómo se hace una novela. Based on the results of criticism, we conclude that Unamuno, by playing with the ‘author’s personal tone’ and reducing the plot, intentionally transfers the emphasis on the traditional plot to the procedure of writing. In the same way, it is demonstrated that the linguistic configuration is of primary importance in the analysed texts and that some parts sometimes seem to have an oral character similar to the ‘articulated play’ that Eichenbaum pointed out about Gogol’s narrative. Both findings, besides showing a similarity between the narrative techniques of Unamuno and Gogol, also reinforce the observations of the critics: for Unamuno (in “Y va de cuento...” and Cómo se hace una novela) the way of creating and telling will be more relevant than the plot itself.